Autophagy Controls Nrf2-Mediated Dichotomy in Pressure Overloaded Hearts - Wu, Weiwei; Qin, Qingyun; Ding, Yan; Zang, Huimei; Li, Dong-Sheng; Nagarkatti, Mitzi; Nagarkatti, Prakash; Wang, Wenjuan; Wang, Xuejun; Cui, Taixing (Frontiers in Physiology, 2021)
Burgeoning evidence has indicated that normal autophagy is required for nuclear factor erythroid 2-related factor (Nrf2)-mediated cardiac protection whereas autophagy inhibition turns on Nrf2-mediated myocardial damage and dysfunction in a setting of pressure overload (PO). However, such a concept remains to be fully established by a careful genetic interrogation in vivo. This study was designed to validate the hypothesis using a mouse model of PO-induced cardiomyopathy and heart failure, in which cardiac autophagy and/or Nrf2 activity are genetically inhibited. Myocardial autophagy inhibition was induced by cardiomyocyte-restricted (CR) knockout (KO) of autophagy related (Atg) 5 (CR-Atg5KO) in adult mice. CR-Atg5KO impaired cardiac adaptations while exacerbating cardiac maladaptive responses in the setting of PO. Notably, it also turned off Nrf2-mediated defense while switching on Nrf2-operated tissue damage in PO hearts. In addition, cardiac autophagy inhibition selectively inactivated extracellular signal regulated kinase (ERK), which coincided with increased nuclear accumulation of Nrf2 and decreased nuclear translocation of activated ERK in cardiomyocytes in PO hearts. Mechanistic investigation revealed that autophagy is required for the activation of ERK, which suppresses Nrf2-driven expression of angiotensinogen in cardiomyocytes. Taken together, these results provide direct evidence consolidating the notion that normal autophagy enables Nrf2-operated adaptation while switching off Nrf2-mediated maladaptive responses in PO hearts partly through suppressing Nrf2-driven angiotensinogen expression in cardiomyocytes.